El femicidio como delito y falso instrumento de prevención: lectura histórica, socio jurídica y política - Benavídez Narváez, Diego Germán (2019)
The definition of femicide has not reduced the death of women, nor has it allowed evidence that criminal mechanisms, such as general prevention, are effective. To this, is added the conjunctural moment that the Ecuadorian legal system has been going through for several years: criminal populism is growing and it argues that the creation of new crimes and the hardening of sentences are the best tools to address such a complex and structural problem, as is violence against women. Statistics show that, the number of cases of femicide in Ecuador has been increasing since its classification, which makes it clear that its inclusion as a crime in the criminal field has been a smoke screen, that disguises and conceals a total fallacy, both legally and statistically, that ends up harming precisely those who seek to defend: women.